Application of Digital Literacy-Based Learning Media to Improve Students' Understanding of Concepts in Social Sciences Subjects - Rostati, Rostati; Gufran, Gufran (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to increase students' understanding of concepts in Social Sciences (IPS) subjects through the application of digital literacy-based learning media in class VIII of SMP Negeri 3 Belo. The research background shows that social studies learning is still centred on teachers with students who tend to be passive, resulting in a lack of understanding of the material, especially those that require memorization. The research method used was Classroom Action Research (PTK) with research subjects of 29 students. This research involved two cycles of action with results showing a significant increase in students' conceptual understanding after implementing digital literacy-based learning media. In cycle I, action I, only 41.93% of students completed it, but this increased to 100% in cycle II, action II. The average student score also increased from 52.19 before the research to 82.52 after the research. The results of this research show that digital literacy-based learning media is effective in increasing students' conceptual understanding and can be applied not only to social studies subjects but also to other subjects at various levels of education.